The Influence Of Factors In Dental Practice: Price, Facilities, Dentist Services, Staff Services, And Word Of Mouth With Patient Satisfaction And Patient Loyalty As Mediators At YDC Dental Clinic, East Jakarta - Stephanie, Skolastika Stephanie; Hutabarat, Zoel (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
dentist services, and staff services, on word of mouth, with patient satisfaction and patient loyalty as mediators at YDC Dental Clinic. This research involved 181 patients. Data collection was carried out by distributing questionnaires containing 35 questions using a 1-5 Likert Scale based on a purposive sampling technique. Data were analyzed using the PLS-SEM method. The results of this study indicate that Price, Facilities, Dentist Services, and Staff Services positively and significantly influence Patient Satisfaction. Furthermore, Patient Satisfaction was proven to have a positive and significant effect on both Patient Loyalty and Word of Mouth. Additionally, Patient Loyalty also has a positive and significant influence on Word of Mouth. Although some service dimensions (Facilities and Dentist Services) did not show a direct significant influence on loyalty, the mediating role of Patient Satisfaction is crucial in shaping loyalty and word of mouth across all examined service dimensions. These findings affirm that patient satisfaction is the primary foundation driving loyalty and word-of-mouth promotion within the context of dental healthcare services.